A new insight into utilization of red mud in poly(vinyl chloride) composites via surface modification and toughening modulation to attain performance optimization. (23rd May 2022) - Ding, Chong; Zhang, Youpeng; Zhang, Na; Di, Xiangyun; Li, Yi; Zhang, Yihe
Graphical abstract: Highlights: RM can improve thermal stability of PVC composites. mRM/PVC composites present better mechanical properties and thermal stability. CPE helps to enhance impact strength of mRM/PVC composites. Performance is optimized via surface modification and toughening modulation. Abstract: Red mud, known as bauxite residue, is a tough solid waste posing a hazardous threat to the environment. It is urgent to develop efficient methods for the utilization of red mud worldwide. In this work, polyvinyl chloride (PVC) composites were filled with red mud (RM). Titanate coupling agent was employed to make surface modification of RM. The influence of RM loading fractions on the performance of PVC composites was evaluated by mechanical test, rheological behavior, as well as thermal stability. The results indicate that RM can improve the thermal stability of PVC composites. However, the rheology curves present an enhancement of plasticizing time and equilibrium torque with the increment of RM loading fraction, indicating the worse processing performance. It appears a decrease of tensile and flexural strength as well as an initial increase and then decrease of impact strength, with the increase of RM loading fraction. In comparison to RM/PVC composites, PVC composites filled with modified RM (mRM) present better mechanical properties and thermal stability. Moreover, the investigation of toughening modulation suggests that chlorinated polyethylene (CPE) accelerates the plastic deformation of PVC matrix under rapid impact, yielding an increment of impact strength in mRM/PVC composites.